The use of everyday and assistive technology in the lives of older autistic adults. (August 2022) - Zheng, Lidan; Foley, Kitty-Rose; Grove, Rachel; Elley, Kieran; Brown, Scott Andrew; Leong, Dawn-joy; Li, Xue; Pellicano, Elizabeth; Trollor, Julian N; Hwang, Ye In (Jane)
Assistive technologies have the potential to provide accessible support to people with varying needs and abilities, including older autistic adults. However, there is currently limited knowledge about how older autistic adults use technology in their daily lives, whether it is sufficient to meet their needs and whether they experience any barriers to technology use. To address these questions, we conducted semi-structured interviews with 15 autistic adults aged over 50 years. Using thematic analysis, we identified two major themes related to how older autistic adults use technology: 'Helping to Manage the External Environment' and 'Increasing Everyday Accessibility and Convenience'. Overall, participants reported experiencing a number of challenges associated with performing everyday activities and while technology was able to offer some assistance, a number of gaps still remain in meeting the support needs of this population. Based on these findings, we offer some guidelines and recommendations for technology use with this population to guide future research and practice. Lay abstract: Technology has the potential to help people with various support needs live more autonomous lives. This includes autistic individuals. In this article, we look at how older autistic adults use technology in their daily lives. Past research examining technology use and autism has mainly focused on helping children to learn new skills. To date, very little research has been conducted looking at how to create and design technology for use by older autistic adults. This is concerning because older autistic adults will likely have supports needs that match or exceed those of similarly aged non-autistic individuals. In this article, we spoke to autistic adults over 50 years about their daily experiences and how they use technology. We identified some important ways that older autistic adults use technology in their daily lives, as well as a number of support needs and barriers to technology use. Based on the findings, we were able to provide some guidelines and recommendations for technology developers and service providers to assist with designing, creating and using technology with older autistic adults.